A Meta-Analysis of Efficacy of Micafungin in Comparison to Amphotericin B, Fluconazole, Voriconazole, and Caspofunginfor the Treatment of Aspergillosis and Candidiasis - Mohammad Jaffar Sadiq Mantargi; Atef H. Aljahdaly; Saleh Hamood Almaymoni; Almotairi, Abdulaziz Safar; Saad Mohammed Alshehri; Emad Abdullah Alhejiri; Ahmed Salem Alghanmi; Ibrahim owash Ahmad Al Harbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The increased invasive fungal infections such as aspergillosis and candidiasis in immune compromised individuals calls for the development of effective antifungal agent. Aim: To develop evidence-based references for best management of invasive fungal infections, eventually guiding clinical practice and enhancing patient care. Methods: A thorough literature review was conducted in PubMed, Embase and Scopus databases ranging for a period from January 2010 to May 2024, focusing on randomised control trials, clinical trials and cohort studies. The primary target was the human studies those include the comparison of micafungin, amphotericin B, fluconazole, voriconazole and caspofungin employed in the treatment of aspergillosis and candidiasis. All the authors took part in extracting the study data and random effects model was chosen to synthesise the results. Results: Eleven studies those fulfilled the inclusion criteria including a total of 3488 participants were selected. Micafungin produced a statistically significant increase in the rate of successful outcomes in comparison to other antifungal agents displaying an odds ratio of 1.358 (95% CI, 1.059 – 1.742, p = 0.016) However, the analysis revealed similar efficacy between micafungin and caspofungin, with a favourable safety profile and lower cases of adverse drug reactions and drug interactions contrast to other antifungal agents. The level heterogeneity among included studies was of moderate level with I2 of 45.38%. Conclusion: Micafungin is a promising antifungal alternative for immunocompromised individuals with aspergillosis and candidiasis due to its efficacy, safety, and minimal adverse drug reactions, but further research is needed.